Guinea-Bissau: from the state supported cinema to the cinema outside of the state - Cunha, Paulo (2017)
We propose to reflect on the civil society, the nation and the State in Guinea-Bissau, through a panoramic analysis of the cinema of Guinea-Bissau over the last five decades. Taking into account Amílcar Cabral´s Cabral initial project, we pay special attention to the production of cinema in Guinea-Bissau in the context of post-colonial African cinema.